2021
DOI: 10.3390/en14227478
|View full text |Cite
|
Sign up to set email alerts
|

Study on Optimum IUPAC Adsorption Isotherm Models Employing Sensitivity of Parameters for Rigorous Adsorption System Performance Evaluation

Abstract: Adsorption cooling technologies driven by low-grade thermal or solar power are used as an energy-efficient alternative to conventional refrigeration and air conditioning systems. Explicit understanding of the adsorption cycles requires precise determination of the performance parameters, replication of the experimental data, and the rigorous study of the adsorption heat transformation method. Hence, the optimum adsorption isotherms model must be identified. Scientists often face difficulties in selecting the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…The BET gas sorption theory can be used for surface area determination in highly specific surface materials and includes the adsorption and desorption process. Based on the IUPAC classification, the results presented in Figure correspond to a type-IV isotherm; the trend of the curve indicates the existence of mesoporous materials . The results reveal that nitrogen volume adsorbed by the aminated microspheres increased rapidly when the pressure was between 0.3 and 0.8 kPa, indicating a vigorous interaction.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The BET gas sorption theory can be used for surface area determination in highly specific surface materials and includes the adsorption and desorption process. Based on the IUPAC classification, the results presented in Figure correspond to a type-IV isotherm; the trend of the curve indicates the existence of mesoporous materials . The results reveal that nitrogen volume adsorbed by the aminated microspheres increased rapidly when the pressure was between 0.3 and 0.8 kPa, indicating a vigorous interaction.…”
Section: Resultsmentioning
confidence: 84%
“…Based on the IUPAC classification, the results presented in Figure 2 correspond to a type-IV isotherm; the trend of the curve indicates the existence of mesoporous materials. 23 The results reveal that nitrogen volume adsorbed by the aminated microspheres increased rapidly when the pressure was between 0.3 and 0.8 kPa, indicating a vigorous interaction. The processes of capillary condensation and evaporation proceeded under different pressures, resulting in an H3 hysteresis loop at pressures greater than 0.9 kPa.…”
Section: ■ Materials and Methodsmentioning
confidence: 92%
“…Characterization and comparison of the textural properties of TiO 2 and P-TiO 2 -0.04 photocatalysts was done using N 2 adsorption/desorption isotherms. The isotherms of the fabricated photocatalysts are determined as type IV with an H 3 hysteresis loop according to IUPAC [43] , indicating mesoporous properties. Moreover, the BET surface area of P-TiO 2 -0.04 ( Table 1 ) is 1.5 times higher than that of pure TiO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…It could be observed from Figure 6 a that the limiting gas uptake over high P/P 0 (0.4–1.0) may be caused by capillary condensation that occurred in pores with monolayer–multilayer adsorption [ 19 ]. Likewise, this feature revealed that the adsorption process of nCPs belonged to IUPAC type IV isotherm [ 42 ]. Collectively, the enhanced physicochemical properties would be conducive to the greater removal performance.…”
Section: Resultsmentioning
confidence: 99%